MicroRNA-585 inhibits human glioma cell proliferation by directly targeting MDM2 - Chen, Wangsheng (Cancer Cell Int, 2020)
BACKGROUND: MicroRNAs (miRNAs) are important regulators for cancer cell proliferation. miR-585 has been shown to inhibit the proliferation of several types of cancer, however, little is known about its role in human glioma cells. METHODS: miR-585 levels in human glioma clinical samples and cell lines were examined by quantitative real-time PCR (qRT-PCR) analysis. Cell proliferation was measured by Cell Counting Kit-8 (CCK-8) and EdU incorporation assays in vitro. For in vivo investigations, U251 cells were intracranially inoculated in BALB/c nude mice and xenografted tumors were visualized by magnetic resonance imaging (MRI). RESULTS: miR-585 expression is downregulated in human glioma tissues and cell lines compared with non-cancerous counterparts. Additionally, miR-585 overexpression inhibits and its knockdown promotes human glioma cell proliferation in vitro. Moreover, miR-585 overexpression also inhibits the growth of glioma xenografts in vivo, suggesting that miR-585 may act as a tumor suppressor to inhibit the proliferation of human glioma. Furthermore, miR-585 directly targets and decreases the expression of oncoprotein murine double minute 2 (MDM2). More importantly, the restoration of MDM2 via enforced overexpression markedly rescues miR-585 inhibitory effect on human glioma cell proliferation, thus demonstrating that targeting MDM2 is a critical mechanism by which miR-585 inhibits human glioma cell proliferation. CONCLUSIONS: Our study unveils the anti-proliferative role of miR-585 in human glioma cells, and also implicates its potential application in clinical therapy.